(untitled) (Research, Society and Development, 2021)
This work aimed to define the best solvent extracting bioactive compounds from the jambo pulp, stored by the methods of freezing and lyophilization. For this purpose, Syzygium malaccensis fruits from the State of Rio Grande do Norte-RN were processed, the pulps obtained were frozen or lyophilized and also physicochemically characterized, while their contents of bioactive compounds were determined. There was a significant increase in the contents of proteins, lipids, ash, reducing sugars, soluble solids, ascorbic acid and total carotenoids of the lyophilized pulp when compared to the frozen one. The lyophilized pulp also presented significantly higher antioxidant activity (24.19 μmol TE g ± 0.09) than the frozen one (17.10 μmol TE g-1 ± 0.56) and satisfactory solubility results (67.03%) and hygroscopicity (9.38%). The contents of yellow flavonoids, total monomeric anthocyanins and total phenolic compounds varied according to the type of solvent used and the proportion of their mixtures. 1.5 M methanol-HCl was the most effective solvent for extracting total phenolic compounds and anthocyanins, while pure water stood out for extracting yellow flavonoids. Both processes indicated that jambo is a source of bioactive compounds, however, lyophilization better preserved the stability of the studied compounds, suggesting this method as the most appropriate for obtaining jambo pulp, in order to better preserve its functional potential fruit.